California Polytechnic Director Leroy Anderson - McCurry::::::photographer::: (1905)
Photograph of Cal Poly's first director, Leroy Anderson, who served from 1903-1907. This is a detail from a photo that was published in the January 1906 Polytechnic Journal, which is described as "Faculty and Students of Polytechnic, 1905." The caption on this print reads: 'Dir. Leroy Anderson - Cal Poly's first chief administrator.'